Thermodynamic Analysis and Optimization of Secondary Overheating Parameters in Turbo-Expander Plants on Low Boiling Working Fluids - A. V. Ovsyannik; V. P. Kliuchinski (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper presents a thermodynamic analysis of secondary overheating in turbo-expander plants on low-boiling working fluids. The possibility of optimizing the parameters of the working fluid in a secondary stem superheater has been studied. The research was carried out for two typical turbo-expander cycles: with a heat exchanger at the outlet of the turbo-expander, intended for cooling an overheated low-boiling working fluid, and without a heat exchanger. Cycles in T–s coordinates were constructed for the studied schemes. The influence of pressure and temperature in the intermediate superheater on the exergetic efficiency of the turbo-expander unit was studied. Thus, the dependences of the exergetic efficiency and losses on the elements of the turbo-expander cycle are obtained when the temperature of the working fluid changes and pressure of the working fluid not changes in the intermediate superheater, and when the pressure changes and the temperature does not change. As a low-boiling working fluid, the ozone-safe freon R236EA is considered, which has a “dry” saturation line characteristic, zero ozone layer destruction potential, and a global warming potential equal to 1370. It has been determined that increasing the parameters of the low-boiling working fluid in front of the low-pressure turbo expander (regardless of the scheme of the turbo expander cycle) does not always cause an increase in the exergetic efficiency. Thus, overheating of the working fluid at a pressure exceeding the critical pressure causes a positive exergetic effect, but for each temperature there is an optimal pressure at which the efficiency will be maximum. At a pressure below the critical pressure, overheating leads to a decrease in the exergetic efficiency, and the maximum exergetic effect is achieved in the absence of a secondary steam superheater. All other things being equal, a turbo-expander cycle with a heat exchanger is more efficient than without it over the entire temperature range and pressure of the low-boiling working fluid under study.